Country level climate risk profiles guide USD 250 million investment in Kenya - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Agriculture represents a large part of Kenya’s gross domestic product (GDP). The International Center for Tropical Agriculture (CIAT) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) developed a national climate-smart agriculture (CSA) profile for the World Bank and the government, which contributed to the design of the Kenya Climate-Smart Agriculture Project (KCSAP). The climates and farming situations vary greatly across Kenya. To set priorities within the country, the World Bank asked CIAT and CCAFS to develop a set of more context-specific county-level climate risk profiles. These helped to guide the USD 250 million investment of the World Bank in KSCAP.